Local Wisdom-Based Tourism Development Strategy at the Ke'te' Kesu' Tourism Object, North Toraja Regency - Abedneigo Carter Rambulangi; Agustinus Mantong; Dina Ramba; Stefani M Palimbong; Wilma D. Ardiyanti; Winta Panimba; Marniati Marniati (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2025)
This study aims to determine the Local Wisdom-Based Tourism Development Strategy at the Ke'te' Kesu' Tourist Attraction, North Toraja Regency . The data analysis techniques used in this study are data reduction, data presentation, and conclusion drawing. From the results of the study, it is known that : (1) The resources at the Ke'te' Kesu' Tourist Attraction are one of the livelihoods of family groups and communities living around the Ke'te' Kesu' Tourist Attraction. (2) Funding sources at the Ke'te' Kesu' Tourist Attraction are obtained from entrance fees without assistance from other social services . (3) The Information System at the Ke'te' Kesu' Object is one of the world-famous tourist destinations and is known by both foreign and local tourists. (4) Utilization of Facilities at the Ke'te' Kesu' Tourist Attraction has various facilities that can be used by tourists who come to visit. (5) Existing Values and Norms It is very necessary to uphold the customs that exist in a region, as well as the need to maintain ethics and also obey the values and norms that exist in a region. (6) How to Maintain Existing Local Wisdom It is necessary to maintain and preserve existing local wisdom so that it is maintained and protected from theft.